2016
DOI: 10.1056/nejmoa1509024
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Dexamethasone in HIV-Associated Cryptococcal Meningitis

Abstract: BACKGROUNDCryptococcal meningitis associated with human immunodeficiency virus (HIV) infection causes more than 600,000 deaths each year worldwide. Treatment has changed little in 20 years, and there are no imminent new anticryptococcal agents. The use of adjuvant glucocorticoids reduces mortality among patients with other forms of meningitis in some populations, but their use is untested in patients with cryptococcal meningitis. METHODSIn this double-blind, randomized, placebo-controlled trial, we recruited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
223
2
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(239 citation statements)
references
References 28 publications
10
223
2
4
Order By: Relevance
“…Also supportive of the generalizability of the results was the finding that mortality in the 2-week amphotericin B-fluconazole group (41.3% at 10 weeks) was the same as that seen in the placebo group of the recent multicenter trial of adjunctive glucocorticoids in which the same antifungal regimen was used. 20 The results were consistent with those in animal models and in our phase 2 studies [10][11][12][13] and may reflect, at least in part, a balance between the rate of clearance of infection and the drug-related side effects. Flucytosine as the partner drug with amphotericin B was associated with more rapid clearance of infection than fluconazole and had a similar side-effect profile, as was previously shown in a study in Vietnam.…”
Section: Discussionsupporting
confidence: 87%
“…Also supportive of the generalizability of the results was the finding that mortality in the 2-week amphotericin B-fluconazole group (41.3% at 10 weeks) was the same as that seen in the placebo group of the recent multicenter trial of adjunctive glucocorticoids in which the same antifungal regimen was used. 20 The results were consistent with those in animal models and in our phase 2 studies [10][11][12][13] and may reflect, at least in part, a balance between the rate of clearance of infection and the drug-related side effects. Flucytosine as the partner drug with amphotericin B was associated with more rapid clearance of infection than fluconazole and had a similar side-effect profile, as was previously shown in a study in Vietnam.…”
Section: Discussionsupporting
confidence: 87%
“…In these patients, treatment strategies must strike a balance between activation of antifungal T cell responses and limiting CNS damage due to inflammation. Although indiscriminate use of steroids is not universally justified for all cases of cryptococcal meningitis (54), including initial treatment of most HIV-infected patients where the immune response is generally poor and microbiological control has not been achieved (55), steroid therapy has been used with some success in refractory cases where elevated levels of IFN-␥, CNS T cell reactivity, and neuronal injury are predominate features of disease, such as in IRIS and PIIRS (6, 11, 27, 28, 32-34, 41, 42). However, a more complete understanding of immune pathogenesis is desperately needed to develop more precise and effective therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, during the first 1 to 2 weeks, 1-2 mg dexamethasone was added to amphotericin B to reduce the infusion-related toxicities of amphotericin B. A recent study showed that dexamethasone is harmful in HIV-associated CM (24). Nevertheless, the dose of dexamethasone in our clinical practice was very small and the duration was relatively short, therefore in our opinion, the negative effects of dexamethasone were negligible.…”
Section: Discussionmentioning
confidence: 87%